Influence of arbuscular mycorrhiza on salt tolerance of Kosteletzkya virginica (l.) C. Presl ex A. Gray (Bangladesh Journal of Botany, 2024)
The aim of this study was to investigate the effect of Glomus mosseae (G. mosseae) on Na+ intercept ability in root tissues of Kosteletzkya virginica (K. avirginica) grown under salt stress. Pot experiments in greenhouse were carried out in K. avirginica inoculated with Glomus mosseae under 1% NaCl stress. The Na+, K+ concentrations, distribution and growth parameters of K. avirginica were analyzed. Salinization reduced phosphorus (P) and chlorophyll contents, root and shoot dry weight. Salinity dramatically increased Na+ concentrations, but decreased K+ contents and K+ / Na+ ratio in shoot and root significantly (p < 0.05). Inoculated plants showed higher P concentrations, dry weight in both roots and shoots than non-inoculated ones. Compared with non-inoculated plants, G. mosseae inoculation accumulated Na+ mainly in the roots, and maintained higher K+ / Na+ ratio in the shoots. The X-ray microanalysis of root transverse section showed that roots endoderm of inoculated plants could strongly retain the transport of Na+ to stellar parenchyma vessels maintaining more Na+ in the roots whereas keep higher K+ / Na+ ratio in the shoots than that of non-inoculated seedlings. The elevated Na+ intercept ability in root tissues of mycorrhizal plants may help in improving the tolerance of K. avirginica to salt stress.Bangladesh J. Bot. 53(4): 1081-1087, 2024 (December)